Impact of Radiation-induced Trismus on Patients’ Life Quality - , Efsun Somay, Busra Yilmaz, Ahmet Kucuk, Erkan Topkan (Archives of Current Research International, 2022)
Head and neck cancers (HNC) account for 10–15% of all cancers globally. Curative radiation therapy (RT) and concurrent chemoradiotherapy (CCRT) with or without surgery are widely accepted standard treatment modalities for these patients. Radiation-induced fibrosis is one of the side effects of these treatments, and it causes degeneration, inflammation, pain, and atrophy of the masticatory muscle fibers and the temporomandibular joint, resulting in trismus. Trismus, also known as hypomobility of the mouth, is defined as a restricted opening of the mouth. Radiation-induced trismus (RIT) can occur within the first three months of treatment or up to 12–48 months later during the follow-up period. It has a significant negative influence on daily activities and vital oral functions, including speech problems, difficulty eating or drinking, psychological problems, malnutrition, dehydration, and difficulty with oral hygiene, reducing the quality of life (QoL). Given the underappreciated nature of trismus and its negative consequences in HNC patients receiving RT or C-CRT, the purpose of this review was to provide a concise review of the physical, social, and emotional implications of RIT and their impact on QoL measures, as well as the available evaluation methods for physicians in the related medical fields.